Benefícios fiscais como incentivo ao desenvolvimento sustentável: uma análise do papel do FDI e da ZPE na promoção do desenvolvimento no Ceará - Santos, Rafaelly Oliveira Freire dos (2023)
The present work aims to answer whether the two main groups of tax benefits granted in the territory of the State of Ceará, notably FDI and ZPE, contribute to the sustainable development of the State. The answer to this question was obtained through three central analyses. In the first, assumptions of Douglas North's theory of institutions were sought in order to understand the relationship between institutions and development. This theory leads to the conclusion that institutional change, that is, in the rules of the game, is the driving force behind development. This being understood as the process of transition from a society in which legislation creates privileges to a society of free competition, in which rules reduce discrepancies in market opportunities. This movement, for North, is what makes a better economic performance possible. With this theoretical assumption, we set out to examine the norms for granting tax incentives within the State of Ceará, noting that both, to a greater or lesser extent: i) are permeated by gaps that confer a relevant degree of discretion to granting agents; ii) they are not endowed with objective criteria for evaluating the costs and benefits of the incentives granted; iii) they do not provide broad transparency of the concession process, nor of the performance of the beneficiary agents. Finally, in the last analysis carried out, it was found that efficient tax benefits in attracting investments depend on legislative changes that allow: i) prior analysis of the costs and benefits of incentives; ii) reduction of discretion in the concession process, through the adoption of automatic criteria; iii) adoption of a single legal body that regulates these incentives, reducing the chances of loopholes and antinomies; iv) direction of incentives for the generation of objectively established positive externalities, especially in the case of the EPZ. In this context, it was suggested as an option the adoption of norms that direct the benefits to economic sectors with greater potential for generating positive externalities, that is, those with higher average wages and lower emission of greenhouse gases.